KONSUMSI JUS DAUN KELOR TERHADAP PENINGKATAN KADAR HEMOGLOBIN (Hb) PADA REMAJA PUTRI DI DESA KALEKE - Maineny, Arie; Muliani, Muliani; Angreni, Reski (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2022)
Abstract: Hemoglobin is a protein that is rich in iron and has an affinity for oxygen, so iron absorption must be maximized if you want to increase hemoglobin levels. At the Kaleke Health Center in the Youth Posyandu program, 56 (35%) teenagers were found to be anemic. The purpose of this study was to determine the effect of consumption of Moringa leaf juice on increasing hemoglobin levels in adolescent girls in Kaleke Village, Dolo Barat District, Sigi Regency. The research design was a quasi-experimental, pretest-posttest research design with a control group. The sample in this study amounted to 30 respondents divided into 2 groups with the sampling technique used was purposive sampling. The research instrument used a measuring tool for Hb Bloodtest levels (Quick-Check Set) and observation sheets. Bivariate analysis using Paired sample t-test. There was an increase in hemoglobin levels in adolescent girls (p=0.011) in Kaleke village. The results showed that young women who consumed Moringa juice tended to experience an increase in hemoglobin levels of 11 respondents, in contrast to young women who did not consume Moringa juice, which tended not to increase by 9 respondents. There is an effect of consumption of Moringa leaf juice on increasing hemoglobin levels in adolescent girls. Puskesmas Kaleke in order to be able to socialize either in posyandu or community visits during treatment about the importance of consuming Moringa leaves.Abstrak: Hemoglobin adalah protein yang kaya akan zat besi memiliki afinitas (daya gabung) terhadap oksigen dengan demikian penyerapan zat besi harus maksimal jika ingin meningkatkan kadar hemoglobin. Di Puskesmas Kaleke pada program posyandu Remaja melakukan pemeriksaan ditemukan 56 (35%) remaja yang mengalami anemia. Tujuan penelitian untuk mengetahui pengaruh konsumsi jus daun kelor terhadap peningkatan kadar hemoglobin pada remaja putri di desa Kaleke Kecamatan Dolo Barat Kabupaten Sigi. Desain penelitian adalah quasy eksperiment, rancangan penelitian pretest-posttest dengan kelompok kontrol. Sampel dalam penelitian ini berjumlah 30 responden terbagi menjadi 2 kelompok dengan teknik pengambilan sampel yang digunakan adalah purposive sampling. Instrumen penelitian menggunakan alat ukur kadar Hb Bloodtest (Quick-Check Set) dan lembar observasi. Analisis bivariat menggunakan uji Paired sample t-test. Terdapat peningkatan kadar hemoglobin pada remaja putri (p=0,011) di desa Kaleke. Hasil penelitian menunjukan remaja putri yang mengkonsumsi jus kelor cenderung mengalami peningkatan kadar hemoglobin sebanyak 11 responden, berbanding terbalik dengan remaja putri yang tidak mengkonsumsi jus kelor cenderung tidak mengalam peningkatan sebanyak 9 responden. Ada pengaruh konsumsi jus daun kelor terhadap peningkatan kadar hemoglobin pada remaja putri. Puskesmas Kaleke agar dapat mensosialisasikan baik dalam posyandu atau kunjungan masyarakat saat berobat tentang pentingnya mengkonsumsi daun kelor.